Pengaruh Financial Stability dan Nature of Industry terhadap Financial Statement Fraud - Fadhilah, Aulia Shafa Nur; Ritonga, Ferdiansyah (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study was conducted to explain and determine the impact of financial stability and industry characteristics on financial statement fraud. Financial stability is measured by the asset turnover ratio, and industry characteristics are measured by the accounts receivable turnover ratio. Companies within the non-cyclical consumer category that are listed on the Indonesia Stock Exchange come from 2020 to 2023 are the subjects of this research. 127 companies are the research population. The sampling method used is proportionate stratified random sampling, and the total sample is 89 companies. This research uses a verification and descriptive approach. Data were analyzed using descriptive statistics and multiple linear regression analysis. The research results show that: (1) the average sample company has an f score value of 0.000, indicating that they can be predicted to commit fraud in their financial statements. (2) The average financial stability condition of the companies increased by 11% of total assets. (3) Conversely, the industry nature experienced a decrease of 0.08% when viewed from receivables.